The Confucian view of the Confucian Catholics in the late Ming Dynasty - Weizhou JIA (Journal of Research for Christianity in China (JRCC), 2024)
Confucian Catholics in the late Ming Dynasty all have a double background, psychology into the school, based on the reflection on the predicament of Confucianism, Buddhism and Confucianism in the Lord, pro ancient Confucianism, Confucianism and Confucianism to the exclusion of nearly, Catholic classic two-way interpretation, reconstruction of Confucian tradition.